TEST RESULTS DATA PROCESSING APPLICATION IN A NEW STUDENT SMU NEGERI 3 SLAWI USING MICROSOFT VISUAL BASIC 6.0 - Andi Maulana Ibrohim; Ire Puspa Wardhani, SKom, MMSi (Jurnal Sistem Informasi, 2005)
In scientific writing, the writer explains the data processing application program prenacangan entrance test results of new students at SMU Negeri 3 Slawi using Microsof Visual Basic 6.0. This application program consists of four forms. And use the program Active Data Object for the database. In the end, the data processing application program of new student entrance test results will be applicable at SMU Negeri 3 Slawi country to facilitate the implementation of new student activities and creating reports.